O ensino da matemática na educação física - Ambrosio, Gislaine Vieira Fuzati; Borges, Kairozan de Oliveira; Silvério, Agda Rodrigues Rios; Lima, Eliene Xavier de; Oliveira, Maria Auxiliadora de (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf